Analisa Berat Isi Dan Kuat Tekan Bata Ringan Menggunakan Foam Agent dengan Bahan Tambah Serbuk Gypsum - Eko Prayitno (SIMETRIS, 2021)
The development of science and human creativity in the construction sector today has found a lot of time efficient technology and implementation that can reduce the budget for work costs. Among these technologies is the discovery and use of light bricks as construction walls. In this research, a light brick was made using foam agent as an added material. While the fine aggregate used is Bengawan Solo River sand with grading of sand that has passed a certain filter and Mount sand from Muntilan as well as gypsum powder added material. The purpose of this study was to determine the effect of the addition of foam agent and gypsum powder to the weight and compressive strength of lightweight bricks with a mixture of cement: Bengawan Solo river sand and cement mixture: mountain sand from Muntilan. The method used is to make a test object with a size of 5 cm × 5 cm × 5 cm. The results showed that the weight of light bricks with a foam agent mixture of 0.8% with added gypsum powder was 6.76% heavier using a mixture with Mount Muntilan sand than using Bengawan Solo river sand which only reached 1231.47 kg / m3. . While the compressive strength characteristics of lightweight bricks using gypsum powder added material using a 0.8% foam agent obtained 3.05% higher yields using a mixture of Mount Muntilan sand than using Solo River sand which only reached 10.82 MPa.